Effectiveness of Life Skill-Based Physical Education on Students’ Movement Skills and Social Values - Kuswoyo, Dili Dwi; Shareef, Qays Banwan (Champions: Education Journal of Sport, Health, and Recreation, 2025)
This study aimed to examine the effectiveness of life skill-based Physical Education (PE) in improving students’ movement skills and social values. The research employed a quasi-experimental design using a pretest–posttest control group. Participants were 60 junior high school students in Merauke, divided into experimental and control groups. The experimental group received PE learning that integrated life skill elements such as cooperation, responsibility, and communication, while the control group followed conventional instruction. Data were collected through standardized movement skill tests and validated questionnaires on social values. The results showed a significant improvement in both movement skills and social values among students in the experimental group compared to the control group (p < 0.05). The findings indicate that incorporating life skills into PE lessons not only enhances physical performance but also develops students’ social competencies. This study suggests that life skill-based PE can serve as an effective approach to fostering holistic student development within the Merdeka Belajar curriculum framework. These findings provide practical guidance for physical education teachers in designing more effective learning activities to enhance students’ fundamental movement skills and social values.